Evaluation Of the Cost of Pulmonary TB and Pneumonia Therapy Based On INA-CBGS - Jessica Lise Hanna; Johannes Bastira Ginting; Sri Lestari Nasution (CV. Inara, 2023)
Tuberculosis as a disease caused by Mycobacterium tuberculosis. Tuberculosis can attack the lungs and can attack all parts of the body. Just as Pneumonia is a respiratory infection that most often causes death in infants and toddlers. The purpose of this study was to evaluate the cost of Pulmonary TB and Pneumonia therapy for the period July 2020 to July 2021 Based on INA-CBGs at RSU Royal Prima Medan. This type of research is descriptive with a qualitative approach. The sample in this study were informants consisting of officers in the INA-CBGs tariff coding section, pulmonary specialists, administrative management staff/staff and patients who were treating pulmonary tuberculosis and pneumonia. The determination of informants was carried out by purposive sampling. Analysis of research data using source triangulation, method triangulation and time triangulation. The results of the study show that the direct costs of patients for pulmonary TB therapy are based on the INA-CBGs rates, these costs are distributed into several costs such as registration fees, consultation fees, laboratory fees, drug costs and X-ray fees. Indirect costs incurred for pulmonary TB therapy patients and indirect costs incurred for pneumonia therapy patients who undergo therapy at RSU Royal Prima Medan. This fee is the sum of transportation costs, food costs, losses due to leave, patient care costs, and drug costs that are not available at the hospital. The duration of therapy for pulmonary TB patients at RSU Royal Prima Medan was in the majority > 5 days in 23 (65.7%) patients, and 1-5 days in 12 (34.3%) patients. The majority of Pneumonia patients at RSU Royal Prima Medan spent 1-5 days in 24 (68.6%) patients, and > 5 days in 11 (31.4%) patients.